Investigation of Rectifier Circuit Configurations for Microwave Power Transmission System Operating at S Band - Chuc Huu Doan; Duong Gia Bach (International Journal of Electrical and Computer Engineering (IJECE), 2015)
The purpose of this work is to propose rectifier circuit topologies for microwave power transmission system operating at ISM band. This paper particularly presents in detail the proposed rectifier circuit configurations including series diode half wave rectifier and voltage doubler rectifier. The maximum conversion efficiency of rectifier using series diode half wave rectifier is 40.17 % with 220 W load resistance whereas it is 70.06 % with 330 W load resistance for voltage doubler rectifier. Compared to the series rectifier circuit, it is significant to note that the voltage doubler rectifier circuit has higher efficiency. The circuits presented are tuned for a center frequency of 2.45 GHz. The rectifiers were fabricated using microstrip technology. The design, fabrication and measurement results were obtained using a well-known professional design software for microwave engineering, Advanced Design System 2009 (ADS 2009). All design and measurement results will be reported.